Hungarian Monitoring, 24 October 1989 . [Magyar rádiófigyelő], 1989. október 24 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - On the situation in the GDR, demonstration after Krenz's election - Shevardnadze's Warsaw talks - Armed forces in Karabakh - Viennese arms reduction talks Domestic Affairs: - Anti-Soviet atmosphere at October 23 commemorations - Kohl's interview to Hungarian Radio - Rezső Nyers writes open letter to former Hungarian Socialist Workers' Party (MSZMP) members on the new party's aims - Hungarian Socialist Party (MSZP) calls opposition parties and organizations to social roundtable - Move to instigate retrial in the Pócspetri police murder case - National minorities Economy: - Tax plans Külpolitika: - Az NDK-beli helyzetről, tüntetés Krenz megválasztása ellen - Sevardnadze varsói tanácskozásáról - Karhatalmista erők Karabahban - A bécsi haderő csökkentési tárgyalás Belpolitika: - Szovjetellenes hangulat az okt.23-i megemlékezéseken - Kohl interjúja a magyar rádiónak - Nyers Rezső az MSZP elnöke nyílt levelet intézett az egykori MSZMP tagokhoz az új párt céljairól - Társadalmi kerekasztalhoz szólította az ellenzéki pártokat és szervezeteket az MSZP - Perújítási indítvány a pócspetri rendőrgyilkosság ügyében - Nemzeti kisebbségek ügye Gazdaság: - Adótervek